Advancing Disaster Risk Finance in Jamaica - World Bank Group (World Bank, Washington, DC, 2019)
The objective of this report is to make recommendations for the Government of Jamaica (GoJ) for theformulation of a country-specific comprehensive disaster risk finance (DRF) strategy, based on the assessment of the legislative, financial management, fiscal, and insurance market environment in Jamaica.